Novel therapeutic targets in advanced urothelial carcinoma. (February 2016) - Rouanne, Mathieu; Loriot, Yohann; Lebret, Thierry; Soria, Jean-Charles
Abstract: Bladder cancer remains one of the most common and lethal diseases that cause approximately 150, 000 deaths per year worldwide. Over the past two decades, the options currently available to patients with invasive disease remained essentially unchanged and no effective drugs have been approved in that time. Cisplatin-based combination chemotherapy remains the standard of care for first-line systemic treatment of metastatic urothelial carcinoma. However, the major advances in understanding the genetic background of urothelial tumors open up a new therapeutic area. Here, we summarize the current state of development of targeted agents in urothelial cancer; with an emphasis on immune checkpoints inhibitors and FGFR targeted therapies that represent the most promising therapeutic approaches for invasive bladder cancer.